2022
DOI: 10.3389/fpubh.2022.734308
|View full text |Cite
|
Sign up to set email alerts
|

Resilience to COVID-19: Socioeconomic Disadvantage Associated With Positive Caregiver–Youth Communication and Youth Preventative Actions

Abstract: Socioeconomic disadvantage is associated with larger COVID-19 disease burdens and pandemic-related economic impacts. We utilized the longitudinal Adolescent Brain Cognitive Development Study to understand how family- and neighborhood-level socioeconomic disadvantage relate to disease burden, family communication, and preventative responses to the pandemic in over 6,000 youth-caregiver dyads. Data were collected at three timepoints (May–August 2020). Here, we show that both family- and neighborhood-level disadv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 67 publications
3
10
0
Order By: Relevance
“…While caregiver worry covaried with youth worry ( Fig. 1 ), as reported previously ( Marshall et al, 2022 ), caregivers were generally more worried than youth about COVID-19 (Caregivers: M = 2.94, SEM = 0.01; Youth: M = 2.31, SEM = 0.01).…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…While caregiver worry covaried with youth worry ( Fig. 1 ), as reported previously ( Marshall et al, 2022 ), caregivers were generally more worried than youth about COVID-19 (Caregivers: M = 2.94, SEM = 0.01; Youth: M = 2.31, SEM = 0.01).…”
Section: Resultssupporting
confidence: 80%
“…Alternatively, adolescents may be more resilient to external COVID-19-related stressors, in part because caregivers, teachers, and/or mentors may serve as supportive buffers for youth. Indeed, in a previous study, we showed that caregivers of families at greater risk of COVID-19 exposure were engaging in more frequent conversations with their children about COVID-19 risk/prevention and reassurance, with these youth also engaging in more preventative behaviors ( Marshall et al, 2022 ). Associations between family-level COVID-19-related stressors and youth's caregiver-reported externalizing and internalizing symptomatology were also more pronounced when their caregivers showed greater stress and anxiety ( Cohodes et al, 2021 ).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations